2018
DOI: 10.1007/s12471-018-1187-0
|View full text |Cite
|
Sign up to set email alerts
|

e-Transmission of ECGs for expert consultation results in improved triage and treatment of patients with acute ischaemic chest pain by ambulance paramedics

Abstract: AimsIn pre-hospital settings handled by paramedics, identification of patients with myocardial infarction (MI) remains challenging when automated electrocardiogram (ECG) interpretation is inconclusive. We aimed to identify those patients and to get them on the right track to primary percutaneous coronary intervention (PCI).Methods and resultsIn the Rotterdam-Rijnmond region, automated ECG devices on all ambulances were supplemented with a modem, enabling transmission of ECGs for online expert interpretation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Our reported incidence is similar to a prospective cohort study from Sweden, where a prehospital ECG detected STEMI in 20% of patients with suspected acute coronary syndrome [ 19 ]. Also, a Dutch investigation showed a comparable incidence of 24% STEMI diagnosis by prehospital ECG in patients with acute chest pain [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our reported incidence is similar to a prospective cohort study from Sweden, where a prehospital ECG detected STEMI in 20% of patients with suspected acute coronary syndrome [ 19 ]. Also, a Dutch investigation showed a comparable incidence of 24% STEMI diagnosis by prehospital ECG in patients with acute chest pain [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…When arriving at an emergency, paramedics are often first to record and interpret the ECG. Different studies [ 12 , 13 ] have been conducted to compare ECG interpretation accuracy between paramedics and physicians. Mencl et al [ 12 ] found no correlation between training, experience, or confidence in the ability of paramedics to recognize ST-elevation myocardial infarctions.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of patients with acute myocardial infarction continues to be challenging, especially when automated ECG interpretation is inconclusive or misleading. However, a study [ 13 ] has shown that, when the ECG exhibits vagueness, clinician input (using the internet) can improve diagnostic performance and reduce time to treatment. It is well documented that misinterpretation of the ECG can lead to incorrect decision making regarding treatment, such as false activations (rates of up to 36% [ 14 ]) or patients being declined.…”
Section: Introductionmentioning
confidence: 99%
“…When arriving at an emergency, paramedics are often first to record and interpret the ECG. Different studies [12,13] have been conducted to compare ECG interpretation accuracy between paramedics and physicians. Mencl et al [12] found no correlation between training, experience, or confidence in the ability of paramedics to recognize ST-elevation myocardial infarctions.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of patients with acute myocardial infarction continues to be challenging, especially when automated ECG interpretation is inconclusive or misleading. However, a study [13] has shown that, when the ECG exhibits vagueness, clinician input (using the internet) can improve diagnostic performance and reduce time to treatment. It is well documented that misinterpretation of the ECG can lead to incorrect decision making regarding treatment, such as false activations (rates of up to 36% [14]) or patients being declined.…”
Section: Introductionmentioning
confidence: 99%